AN ANALYSIS OF STUDENTS’ MISCONCEPTIONS ON NEWTON’S LAWS USING THE CERTAINTY OF RESPONSE INDEX (CRI) METHOD IN CLASS IX-B OF SMAN 2 PERCUT SEI TUAN - Aulia Febriani Sihombing; Beby Cavana Suwu; Bintang Elisa Sitorus; Eksaudi Elianto Munthe; Nazwa Husna Adira; Reysa Nadine Nasution; Sela Auria Fau; Solikin (SULTAN ADAM: Jurnal Hukum dan Sosial, 2026)
Misunderstanding of Newton’s Laws is one of the main factors contributing to low physics achievement at the senior high school level. These misconceptions are often stable and strongly believed by students, which can hinder further learning, making early identification an important step for improving instruction. This study aims to describe students’ levels of conceptual understanding and misconceptions regarding Newton’s Laws using a diagnostic test based on the Certainty of Response Index (CRI). The research was conducted with 33 tenth-grade students from class X-B at SMA Negeri 2 Percut Sei Tuan using a descriptive quantitative non-experimental design. The instrument consisted of 10 multiple-choice questions accompanied by a CRI scale ranging from 1 to 5, which was used to classify students into categories of understanding the concept, not understanding the concept, lucky guess, and misconception. Data were analyzed based on the combination of correct/incorrect answers and high/low CRI scores. The results indicate that students still experience significant misconceptions in several sub-concepts, particularly concerning action–reaction forces, the identification of forces acting on an object, and the relationship between net force and motion. These misconceptions primarily appear among students who are highly confident in their incorrect answers , with the highest percentage of misconceptions found on Question No. 5 at 72.8%, followed by Questions No. 3 and No. 7, each reaching 57.6%. These findings confirm that the CRI method is effective in diagnosing the quality of student understanding and highlights the need for instructional interventions that focus on correcting faulty conceptual beliefs rather than merely procedural memorization.